Tinjauan Penerapan Sistem Manajemen Keselamatan Dan Kesehatan Kerja (SMK3) Pada Proyek Pembangunan Hotel Novotel Pekanbaru - M Almer Rikardo; Hendra Taufik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Safety and Health Management System (SHMS) was mandatory for construction company in order to protect stakeholder including workers, staff from work accident. The current study aimed at identification stakeholders perception of Hotel Novotel construction on the implementation of SHMS. Further the result of the study was analyzes by comparing to the score established in the Government Regulation act No 50/ 2012.Data analysis were performed by quantitative and qualitative approach quantitative methodes was conducted on hard defences on 17 staff and 108 workers. In the project of Hotel Novotel Construction. Qualitative analysis was done especially on the expert (head of SHMS). It result that the implementation of SHMS account for 66,57% which categorize into “good” in accordance with Goverment Regulation act No 50/ 2012. Based on interview with expert respondent, the implementation of SHMS on the project had on optimal level. However it was found the inefficient in supervision and fund support on the program of SHMS.Keywords: Application, Implementation, Safety, Health Management System (SHMS).